2015
DOI: 10.1016/j.smim.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Early IFN type I response: Learning from microbial evasion strategies

Abstract: Type I interferon (IFN) comprises a class of cytokines first discovered more than 50 years ago and initially characterized for their ability to interfere with viral replication and restrict locally viral propagation. As such, their induction downstream of germ-line encoded pattern recognition receptors (PRRs) upon recognition of pathogen-associated molecular patterns (PAMPs) is a hallmark of the host antiviral response. The acknowledgment that several PAMPs, not just of viral origin, may induce IFN, pinpoints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 260 publications
0
45
0
Order By: Relevance
“…Secreted interferons bind to cell-surface receptors (IFNAR) in an autocrine and paracrine manner and activate specific kinases (TYK2 and JAK). These enzymes phosphorylate and activate key transcription factors (STATs), thereby inducing signal transduction pathways that establish an antiviral response in target cells via activation of interferon-stimulated genes 90 .…”
Section: Candidate Genesmentioning
confidence: 99%
“…Secreted interferons bind to cell-surface receptors (IFNAR) in an autocrine and paracrine manner and activate specific kinases (TYK2 and JAK). These enzymes phosphorylate and activate key transcription factors (STATs), thereby inducing signal transduction pathways that establish an antiviral response in target cells via activation of interferon-stimulated genes 90 .…”
Section: Candidate Genesmentioning
confidence: 99%
“…Interferon (IFN) is a cytokine that induces an antiviral state in cells and influences via host cells (Coccia and Battistini, 2015). IFN is divided into type I, II, and III IFN.…”
Section: Introductionmentioning
confidence: 99%
“…Certain viral pathogens have co-evolved immune evasion strategies in order to survive the battle within the host, affording a selective advantage [24]. For example, the RNA virus of the orthomyxoviridae family, influenza A encodes the viral protein NS1 specifically as an IFN antagonist, which interacts with the IFN-β signaling pathway, blocking IRF3 and the IFN-β promoter, allowing permissive virus infection in the absence of IFN [25].…”
Section: Viral Evasion Of Ifn Responsesmentioning
confidence: 99%
“…Underlying chronic inflammatory diseases such as HIV and HCV project heavy burdens on the host that may not be easily lifted with existing treatments. It has been reported that collectively these viruses have evolved up to ninety evasion strategies of innate immunity facilitating the establishment of chronic inflammation that fuels virus replication [24]. Thus improved therapies, taking into consideration such immune activation sequelae, are urgently needed.…”
Section: Chronic Virus Infectionsmentioning
confidence: 99%